Guidelines for Research Proposal Writing in the Social Sciences - Bhattachan, Krishna Bahadur (Himalayan Journal of Sociology and Anthropology, 2008)
No abstract available Himalayan Journal of Sociology & Anthropology Vol.1 2004 p.99-105